Kepercayaan Dimediasi Kepuasan Pasien terhadap Citra Rumah Sakit - Johanes Tantra Wijaya; Agusdini Banun Saptaningsih; Tantri Yanuar Rahmat Syah (Jurnal Manajemen Kesehatan Indonesia, 2021)
Establishing an excellent hospital image is critical as many people are still experiencing trust issues for hospitals in Indonesia, especially in major cities. A hospital's image comes from its quality of service, the patient's trust in the quality of service, and the patient's satisfaction. This study tries to provide empirical evidence on the effect of quality of service and patient confidence on the hospital's image mediated by patient satisfaction. A quantitative - causality research method is used. Primary data was taken from survey to patients who are taking drugs in the outpatient pharmacy installation unit at Taman Sari Hospital, West Jakarta. This research uses AMOS-path analysis, and the results showed the quality of service and patient's trust had a positive and significant effect on the hospital's image with patient satisfaction as an intervening variable. Partially, the quality of service has a positive and significant effects on both patient satisfaction and hospital image. Patient confidence has a significant positive effect on patient satisfaction but it is insignificant to the hospital's image. Research findings show that a patient's trust has a positive impact on the hospital's image when mediated by patient satisfaction. Suggestions from this research are conducting training, i.e. speed training not to exceed the standard response time as well as competency, skills training and service excellence training for pharmaceutical personnel. Improving the quality of pharmacy facilities such as waiting rooms to make it more comfortable is also suggested